Analysis of factors influencing the technical efficiency of smallholder maize farmers in northern province, Zambia - Mumba, Elijah (School of Economics, 2024)
This study investigated the efficiency of smallholder farmers in Northern Province, Zambia. The research utilized data collected in 2014/2015, which was representative of the province and gathered by the Institute for Agricultural Policy Research Institute in collaboration with the Zambia Statistical Agency and Ministry of Agriculture. To assess technical efficiency, a stochastic production function with a translog functional form was developed. The model included four characteristics related to the farms and farmers, as well as three institutional variables, all of which were found to be statistically significant. The efficiency levels observed ranged from 0.02 to 0.93, with a median value of 0.67. The findings indicated that the primary factors influencing total output were the extent of cultivated land, followed by the use of fertilizers. The empirical analysis demonstrated that access to credit, extension services, and farmer input support programs, as well as the distance between the household's residence and the farm, the gender, age, and educational level of the household head, all played vital roles in determining the technical efficiency at the farm level.